Teoreticko-metodologická východiska institucionální ekonomie - Volejníková Jolana (Univerzita Pardubice, 2010)
The institutional economics itself hold over one hundred years of traditions. Although this line of thought does not comprise the main stream of economic thought, nowadays it is supposed to be one of its important parts. The theoretical benefits of institutionalism lie mainly in recognition of the influence of institutions (formal and informal) in shaping economic behaviour and achievement of economic performance. The article analyzes in detail the theoretical and methodological basic of institutionalism and argues in favour for the application of its scientific knowledge and further development.
Keywords: institutions; American institutionalism; New institutional economics; formal and informal institutions; theoretical and methodological basic